2017
DOI: 10.1021/acs.jpca.7b05996
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Kinetics Analysis for Ḣ Atom Addition to 1,3-Butadiene and Related Reactions on the Ċ4H7 Potential Energy Surface

Abstract: The oxidation chemistry of the simplest conjugated hydrocarbon, 1,3-butadiene, can provide a first step in understanding the role of polyunsaturated hydrocarbons in combustion and, in particular, an understanding of their contribution toward soot formation. On the basis of our previous work on propene and the butene isomers (1-, 2-, and isobutene), it was found that the reaction kinetics of Ḣ-atom addition to the C═C double bond plays a significant role in fuel consumption kinetics and influences the predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…As the flux of the H + C 6 H 5 reaction is 200 times more important than the C 3 H 3 + C 3 H 3 flux, the fulvene and 2-ethynyl-1,3butadiene abundances will be low. Moreover, the H + fulvene and H + 2ethynyl-1,3-butadiene reactions should be relatively fast (around 1.0 × 10 −12 cm 3 molecule −1 s −1 even at 150-200 K), the barrier for the H + fulvene reaction being calculated equal to 7.0 kJ/mol at the M06-2X/AVTZ level (this work) in good agreement with the recent study of H + butadiene by Li et al (2017).…”
supporting
confidence: 91%
“…As the flux of the H + C 6 H 5 reaction is 200 times more important than the C 3 H 3 + C 3 H 3 flux, the fulvene and 2-ethynyl-1,3butadiene abundances will be low. Moreover, the H + fulvene and H + 2ethynyl-1,3-butadiene reactions should be relatively fast (around 1.0 × 10 −12 cm 3 molecule −1 s −1 even at 150-200 K), the barrier for the H + fulvene reaction being calculated equal to 7.0 kJ/mol at the M06-2X/AVTZ level (this work) in good agreement with the recent study of H + butadiene by Li et al (2017).…”
supporting
confidence: 91%
“…Two solvers also showed reasonably good agreement (except the P1 ↔ WDT12 reaction); the difference was found to be 1–2 orders of magnitude, depending on temperature. The very first publication compared the HPL rate constant calculated using the Multiwell and PAPR solvers by Li et al 54 In that paper, some discrepancies were also found between the two solvers. The authors are aware that PAPR is a recently developed solver, indicating that the solver may still require some refinements, compared to MultiWell, The discrepancies obtained in this work constitute useful information which can be communicated to the code developers.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] At higher temperatures, only 1,3-butadiene caught the attention of most researchers. 13,26,27 Li et al 26 measured ignition delay times of 1,3-butadiene in a shock tube and a rapid compression machine. Not surprisingly, they observed a clear lack of NTC region due to the suppression of low-temperature reactivity of 1,3 butadiene.…”
Section: Introductionmentioning
confidence: 99%